The role of lipid peroxidation in the pathogenesis of experimental peritonitis - I. V. Savytskyi; S. G. Znamerovsky; O. F. Dzygal (Kazimierz Wielki University, 2020)
In the first hour simulated fecal peritonitis development in the rats blood revealed an increase in the level of diene conjugates and malondialdehyde (p <0.001 compared with the results of intact animals. In second stage was detected more pronounced increase in the level of primary and secondary products of lipid peroxidation (p <0.001) as compared with the data of the same hole in the first stage, and compared with the results of group No. 1). On the 3rd day of simulated peritonitis development in rats there is a marked deterioration of the animal condition, which was manifested in lipid peroxidation progression: the diene conjugates level increased at the level of significance p <0,001, and the level of malondialdehyde compared to p <0,05 data from the previous stage of the same group.